UAV AND UGV TRACKING SYSTEM FOR CHEMICAL GAS MAPPING - Falih Akbar, Muhamad
Mapping of hazardous chemical gases at different altitudes requires a type of vehicle that can change positions at surface elevations as well as at high altitudes in the air. Therefore, UAV and UGV are used simultaneously in hazardous chemical gas mapping systems. To get map results that are representative of the unit of time, the UAV and UGV must move and change positions simultaneously. Therefore, a system was created where the UAV can follow the UGV autonomously based on GPS coordinates by utilizing the Ardupilot Follow Mode. In this final project, Real Time Kinematics (RTK) GPS will be used to improve GPS accuracy. The experiment show that the system created has succeeded in making the UAV able to follow the UGV with an average distance between the UAV and the UGV of about 1 m.